Money in American politics the first 200 years - Miller, Richard Lawrence 1949- (McFarland & Company, Inc., Publishers, 2021)
"The people who run our government are affected by money just like the rest of us. Over the years, many of these officials have worried about meeting mortgage payments, holding off creditors, and avoiding bankruptcy. Others made fortunes by devoting their time to supervising their business interests. Either way, these distractions affected the lives of everyday citizens--from the price of shirts to the decisions for war or peace. In school, students are taught about governmental principles underlying political controversies, but instructors seldom talk about money that presidents and cabinet members stood to gain or lose, depending on who prevailed in a political dispute. This book will help fill the gaps in that knowledge. To ignore the business activities of our leaders is to ignore most of their adult lives. Having such awareness allows voters to see motivations in government decisions that may otherwise be obscure. Concentrating on presidents and cabinet members, from the birth of the U.S. through the Carter administration, this book tells how they and their associates gained and lost wealth, and how this affected their nation's well-being"--
2106
Keywords: Geschichte 1771-1971; Geschäftsmann; Politiker; Politische Entscheidung; Geld; USA; Campaign funds / United States / History; Money / Political aspects / United States; Banks and banking / Political aspects / United States; Political corruption / United States; United States / Economic conditions / History; United States / Politics and government / History; HISTORY / United States / General; POLITICAL SCIENCE / American Government / Executive Branch; Presidents; United States; History